Factor V Leiden homozygous mutation: Recurrent venous thromboembolism during periods of discontinuation of anticoagulant therapy (Journal of Health Sciences, 2021)
Venous thromboembolism (VTE), also known as deep vein thrombosis and pulmonary thromboembolism, is a medical condition that has a high incidence and a multifactorial pathogenesis. One of the causes is a mutation of the Factor V Leiden (FVL), which is the most common inherited thrombotic disorder. A mutation inherited from both parents is found in about 0.05-0.5% of cases, making our case more medically interesting. We presented the case of a young male patient with recurrent VTE and few risk factors who was admitted to the hospital 4 times with VTE symptoms over a 5-year period. In the background, there was a homozygous FVL mutation and improper use of anticoagulant therapy. We examined the medical data, diagnostics, therapy, and precautions that were and are required.